Banggai cardinalfish conservation: priorities, opportunities, and risks. (April 2019) - Ndobe, S; Moore, A; Yasir, I; Jompa, J
Abstract: Human actions are undoubtedly the major factor affecting the biosphere in this Anthropocene era, making it vital to involve all levels of society in the stewardship of natural resources, in particular marine ecosystems and biodiversity. The Banggai cardinalfish Pterapogon kauderni is a unique species at risk of extinction and an object of global conservation concern. The endemic range of P . kauderni is limited to around 500km2, mostly in the Banggai Archipelago, Central Sulawesi, Indonesia. The objective of this study was to evaluate the priorities for P . kauderni conservation, with a focus on the recently declared Banggai Dalaka MPA, the National Plan of Action (NPOA-BCF) and the decisions taken at CITES CoP 17 in 2016. Risks identified include the loss of genetic diversity and structure, serial depletion of populations/stocks, loss of identity ("branding" issues), local threats to habitat/microhabitat, and the impacts of global change. Opportunities include local, national and international awareness, the CITES Animal Commission processes, iconic status, and stakeholder capacity. Key priorities identified included: (i) prioritise endemic (not introduced) P . kauderni populations; (ii) protect genetic diversity through site/stock-based management (conservation, ornamental fishery, monitoring), initiated using existing genetic population structure data, while seeking to develop a database of genetically unique (reproductively isolated) stocks; (iii) protect and rehabilitate P . kauderni habitat and microhabitat (especially Diadema urchins and sea anemones) within the Banggai Dalaka MPA; (iv) investigate, record (and where necessary restrict) in-country movements of P. kauderni, especially removal from the endemic range (e.g. currently unrecorded shipping to Kendari), as well as export and international movements; (v) regulate and restrict the release of P . kauderni to the wild from captivity and/or between known/suspected genetic stocks; (vi) institutionalisation at multiple levels in a holistic socio-ecological context to provide robust and resilient conservation management and capitalise on the "flagship species" potential of the Banggai cardinalfish.